Evaluation of Nutrient Content of Animal Feed Crops in Tropical Islands Region (Case Study of Tomia Timur District, Wakatobi Regency, Indonesia) - Syamsuddin; Ali Bain; Mardianto; Andi Murlina Tasse; Deki Zulkarnain (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Ruminant livestock raised by the community in Tomia Timur District, Wakatobi Regency, are mainly grazed semi-extensively, with forages that grow wild in the surrounding nature. However, the nutrient content of the forage is not yet explicitly known, which can affect livestock productivity. This study analyzes the nutrient characteristics of forage plants used as animal feed in the Tomia Timur District. This study was conducted for two months, from March to April 2024, through two stages. The first stage was sampling forage in the field. In contrast, the second stage involved analyzing nutrient content at the Animal Feed Technology Unit Laboratory and the Animal Feed Analysis Unit Laboratory, Faculty of Animal Science, Halu Oleo University, Kendari. The research method used was purposive sampling, with data collection through interviews with respondents and field observations. The variables analyzed included dry matter, organic matter, crude protein, and crude fiber. The findings show that most of the greens given to ruminant livestock in Tomia Timur District have a nutrient content good enough to meet the nutritional needs of cattle and goats. The greens analyzed include Callophyllum inophyllum L., Lannea coromandelica (Houtt.) Merr., Strobilanthes crispus, Garuga floribunda Decne., Cassytha filiformis, Ampelopsis heterophylla var. vestita Rehd., Dendrolobium umbellatum (L.) Benth., Syzygium cumini (L.) Skeels, Passiflora foetida, Gliricidia sepium, Bridelia tomentosa Blume, Wikstroemia indica L. C.A. Mey, Ischaemum rugosum (saramollagrass), with varying nutrient content, namely dry matter between 20.34%-44.42%, organic matter 82.68%-96.15%, crude fiber 13.37%-32.83%, and crude protein 6.51%-22.10%. These findings indicate that wild greens in the area have good potential as ruminant livestock feed.